Penyuluhan Pemeriksaan Kesehatan Gratis Pada Masyarakat Terutama Lansia Di Dusun Inruiya Desa Mare-Mare Kecamatan Bontomanai Kab Kep Selayar - Imam Permana; sri wahyuni uni (Pangulu Abdi: Jurnal Pengabdian Kepada Masyarakat, 2022)
With increasing age, physiological function decreases due to the aging process so many non-communicable diseases appear in the elderly. Health is a state of physical, mental, spiritual and social well-being that enables everyone to live a socially and economically productive life. Aging occurs as a result of biochemical changes programmed by DNA molecules and every cell will in time undergo mutations. Aging is a period of change experienced by individuals both physically and psychologically due to decreased body function. This will affect various aspects of life in old age. So that it requires maintenance that is different from the age of children, adolescents, and adults who need support from those around them. This free treatment was carried out in Inruiya Hamlet, Mare-Mare Village, Bontomanai District, Kep Selayar Regency. Treatment is carried out in the form of measuring blood pressure, checking cholesterol, checking uric acid, checking blood sugar, measuring weight and height. Besides that, it was also conveyed how to live a healthy lifestyle in the elderly. This counseling activity lasted for 180 minutes and was carried out in one of the hamlets in Mare-Mare Village, Bontomanai District, Kep Selayar Regency. The purpose of this activity is to check public health, especially the elderly. Counseling in the form of percentages, conducting health checks such as measuring blood pressure, checking blood sugar, checking cholesterol and checking uric acid. The result of this counseling activity is that the elderly are aware of the importance of carrying out health checks, especially measuring blood pressure, checking blood sugar, checking cholesterol and checking uric acid. From the results of the activity, it was found that before carrying out counseling, some elderly people wanted to have their health checked, but due to the distance from the village to the service facility, the elderly only took medicine at the shop to relieve pain. The counseling activities carried out went well, this activity was carried out in the hamlet of Inruiya, one of the hamlets in Mare-Mare Village, which is in the working area of ​​the Polebunging Health Center. It is hoped that the community, especially the elderly, will already know the benefits of carrying out health checks and will make visits and health checks the following month in other hamlets in Mare-Mare Village, Bontomanai District, Kep Selayar Regency.